Advanced GNC-oriented modeling and simulation of Vertical Landing vehicles with fuel slosh dynamics. (March 2023) - Farì, Stefano; Seelbinder, David; Theil, Stephan
Abstract: This paper introduces a flexible framework to enable high-fidelity simulations of the fuel slosh dynamics for verification of the Guidance, Navigation and Control (GNC) algorithms. The sloshing phenomenon must be tackled during the control system design phase and the GNC software run and validated within appropriate simulation frameworks. Equivalent mechanical models can well approximate sloshing under specific assumptions, allowing the derivation of the multibody vehicle's equations of motion; however, while suitable for analysis and control synthesis purposes, this approach presents several limitations for implementation as a simulation model. In this work, the multibody plant embedding slosh dynamics is modeled by means of the DLR's Vertical Landing Vehicles Library (VLVLib) written using the object-oriented Modelica modeling language. The advantages of using Modelica are explored throughout the paper. Given that control synthesis, analyses and simulation campaigns are usually performed in the Matlab/Simulink environment, a core point of the proposed solution is to achieve a good synergy within the latter and the Modelica plant model with the least readaptation burden for the developer. The strategies to achieve a full integration and verification tool chain are illustrated. The potential of this approach is demonstrated via two different test cases: a lunar landing scenario of the ALINA spacecraft developed by PTS, and CALLISTO reusable rocket demonstrator. Highlights: A flexible framework to enable high-fidelity simulations of the fuel slosh dynamics for verification of the GNC algorithms is introduced. The spacecraft model embedding the slosh dynamics is implemented exploiting Modelica language. A GNC testing framework is obtained with the integration of the causal Simulink environment with the compiled Modelica model. Two test cases are presented: the ALINA spacecraft lunar landing scenario and CALLISTO reusable Vertical-Takeoff–Vertical-Landing demonstrative mission.